An overview of austenitic stainless-steel rock anchors damage in an environment rich with chlorides. (June 2019) - Gruttadauria, Andrea; Barella, Silvia; Gerosa, Riccardo
Abstract: The failure of rock anchors in exotic beaches can change a fun climbing holiday into a tragedy: austenitic stainless-steel bolts can break because of an underhand and insidious form of corrosion that does not show itself before it is too late. The failure analyses performed in this study on corroded bolts, the huge amount of information reported in literature and the presence of three unmistakable conditions (material, stress and environment) lead us to think that the eventual damages are due to stress corrosion cracking (SCC), in turn due to an unlucky combination of events. After analysing the corrosion, excluding production mistakes in the base material (e.g. steel sensitization) or during installation into the rock (e.g. galvanic connection), we have characterized commercial AISI 304 L expansion bolts and conducted focused experiments in order to understand the main factors involved with the aim to explain the origin of SCC. After this preliminary part, a specific SCC test has been set up to understand the susceptibility of the commercial bolts. The discriminating factor is the process route in terms of resulting surface finishing and hardness; however, all the bolts show more or less the same resistance to corrosion. Highlights: Stainless-steel rock climbing anchors close to the seaside fail because of corrosion. The RFCA performed suggests the damage origin is crevice which develops itself as stress corrosion cracking. Several tests were developped to understand the corrosion trigger points. The corrosion causes is the steel passive layer breackage due to the bolts installation procedure and/or to the microclimate. Stress corrosion is then supported by residual stress coming both from process and from installation procedure. To prevent the failures, it is necessary to tune up the manicfture process in order to increase the surface properties.